2002
DOI: 10.3171/jns.2002.97.5.1208
|View full text |Cite
|
Sign up to set email alerts
|

Extradural motor cortex stimulation for advanced Parkinson disease

Abstract: Motor cortex stimulation is a minimally invasive surgical procedure used for pain control. The authors report their results treating two patients with typical Parkinson disease. Unilateral motor cortex stimulation proved to be beneficial bilaterally. Motor cortex stimulation may represent a cost-effective alternative to deep brain stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 16 publications
5
46
0
Order By: Relevance
“…However, antidromic cortical activation also provides a common link between these stimulation sites, which are all in proximity with major cortical output pathways. The clinical benefit of epidural cortical stimulation in the MPTP primate model (Drouot et al 2004) and in some human PD patients (Canavero et al 2002) support the hypothesis that direct control of cortical activity is an effective mechanism in alleviating PD symptoms. However, other human PD patient pools derived no benefits from epidural stimulation (Cilia et al 2007), suggesting that this method produces less than robust effects.…”
Section: Clinical Relevance Of Antidromic Cortical Stimulationmentioning
confidence: 71%
“…However, antidromic cortical activation also provides a common link between these stimulation sites, which are all in proximity with major cortical output pathways. The clinical benefit of epidural cortical stimulation in the MPTP primate model (Drouot et al 2004) and in some human PD patients (Canavero et al 2002) support the hypothesis that direct control of cortical activity is an effective mechanism in alleviating PD symptoms. However, other human PD patient pools derived no benefits from epidural stimulation (Cilia et al 2007), suggesting that this method produces less than robust effects.…”
Section: Clinical Relevance Of Antidromic Cortical Stimulationmentioning
confidence: 71%
“…Their work has been focused more on using MCS to treat movement disorders, in particular PD, rather than pain. 18,33,54,55,57,60,63 Results from these studies were promising in early phases. The Italian Neurosurgical Society study group 60 reported on a group of 16 patients, with a postsurgical time of 3-30 months for the 10 patients ultimately analyzed.…”
Section: Introductionmentioning
confidence: 93%
“…A few studies have suggested that this invasive stimulation may be effective in treating the symptoms of some motor disorders (Nguyen et al, 1998) and possibly to be effective for PD as well (Canavero et al, 2002(Canavero et al, , 2003Woolsey et al, 1979). However, other studies found no improvement (Moro et al, 2010).…”
Section: Imaging Tms Effects In Pdmentioning
confidence: 98%